Performance Evaluation of Activated Carbon Produced from Post-Consumer Paper for Wastewater Treatment - Auni Farahiyah Muhamad Waras; Nur Iman Safina Nazrul Izzad; Nur Nadia Natasya Khairul Ariffin; Ahmad Nordin, Norain; Nuramirah Juma’at (Multidisciplinary Applied Research and Innovation, 2026)
Sustainably reusing waste materials offers promising solutions to environmental issues, particularly in the treatment of wastewater. In this study, the performance of activated carbon (AC) made from post-consumer paper in treating wastewater was evaluated using two chemical agents, potassium hydroxide (KOH) and zinc chloride (ZnCl₂), at varying concentrations. The AC was characterized by examining chemical modifications and surface functional groups using Fourier Transform Infrared Spectroscopy (FTIR). Treated wastewater was analyzed for biochemical oxygen demand (BOD), turbidity and pH levels to evaluate the efficiency of the activated carbon. The results showed that ZnCl₂ (1.0 M) achieved the lowest BOD (1.90 mg/L), turbidity (0.21 NTU), and near-neutral pH (7.6), while KOH (1.5 M) resulted in a BOD of 2.10 mg/L and the highest pH of 11.32. Among the two activating agents used, ZnCl₂ showed better performance in treating wastewater compared to KOH. These findings demonstrated the potential of wastepaper as a practical precursor for AC, which could support environmentally friendly water treatment methods and efficient waste disposal.